Instruments to evaluate hospitalised children parents' satisfaction with nursing care: a scoping review - Fernanda Loureiro; Vanessa Antunes (BMJ Publishing Group, 2022)
Aim To identify instruments that allow the evaluation of parent's satisfaction regarding nursing care during their child hospitalisation.Methods A review was performed using Preferred Reporting Items for Scoping Reviews. The study was prospectively registered in Open Science Framework. Research was carried out on EBSCOhost, PubMed, SciELO, Web of Science and ScienceDirect platforms as well as grey literature. Additionally, the references of selected articles were also examined.Results A sample of 65 articles allowed the identifications of 38 distinctive instruments to evaluate parents' satisfaction in different hospital settings. Most studies were applied in paediatric wards (n=28), followed by neonatal intensive care units (n=21), paediatric intensive care units (n=9) and emergency departments (n=7). Sample size ranged from 13 to 3354 and 3 studies used mixed methods, 20 were methodological studies of instruments construction or validation and 43 were quantitative studies. 21 different instruments previously existent were found. In 3 studies, adapted instruments were used and, in 14 studies, structured instruments were purposively designed for the study. Instruments had between 1 and 13 domains and total number of items ranged between 13 and 92. Most studies assessed overall satisfaction (n=53) and instrument reliability (n=49) and/or validity (n=37).Conclusion Most instruments consider nursing care as a domain of satisfaction. Only two instruments focused specifically on nursing care. In most of the studies, there was a concern to evaluate instruments psychometric properties. This review clearly shows that there is still a gap in the literature on the range of aspects that influence satisfaction and a lack of consensus on ideal conditions for instrument use and application.